2000
DOI: 10.1007/s101030050043
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Proteolytic Enzymes from Porphyromonas gingivalis Using Light-activated Agents

Abstract: Previous studies have shown one of the causative agents of periodontitis, Porphyromonas gingivalis, can be killed by red light in the presence of the light-activated antimicrobial agent toluidine blue O (TBO). The purpose of this study was to determine the effects of irradiating the organism with red light in the presence of TBO on its proteolytic enzyme activity.Suspensions of P. gingivalis were exposed to light with a wavelength of 633 nm in the presence of various concentrations of TBO. Samples were taken a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 8 publications
1
29
0
Order By: Relevance
“…This bacterium is also known to degrade hemoglobin for its growth to produce protoporphyrin which could act as an endogenous photosensitizer, making this bacterium photosensitive [28]. In fact, some other studies have also reported the bactericidal effects of laser irradiation on periodontopathogenic bacteria including P. gingivalis [21,23,[27][28][29][30]. These findings suggest the feasibility of PDT for both apical and marginal periodontitis.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…This bacterium is also known to degrade hemoglobin for its growth to produce protoporphyrin which could act as an endogenous photosensitizer, making this bacterium photosensitive [28]. In fact, some other studies have also reported the bactericidal effects of laser irradiation on periodontopathogenic bacteria including P. gingivalis [21,23,[27][28][29][30]. These findings suggest the feasibility of PDT for both apical and marginal periodontitis.…”
Section: Introductionmentioning
confidence: 66%
“…Recently, PDT has been used as an antimicrobial therapy with some photosensitizers to target a variety of microorganisms, such as P. gingivalis, Fusobacterium nucleatum, Propionibacterium acnes, S. aureus, S. mutans, and E. coli [21][22][23][24][25][26]. Guffey and Wilborn reported that 405 nm blue light had a bactericidal effect on two aerobes, Staphylococcus aureus and Pseudomonas aeruginosa [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in the viable counts of P. gingivalis in pure culture at a light dose of 8.8 J was 100% (15). However, when lethal photosensitization of P. gingivalis was carried out in the presence of HGFs using unconjugated TBO, there was only a 0.7-log 10 -unit reduction in P. gingivalis viable counts but a 99% reduction in the incorporation of [ 3 H]Tdr by human cells, a measure of DNA synthesis.…”
Section: Discussionmentioning
confidence: 97%
“…Our previous work has shown that membrane proteins may be affected by lethal photosensitization, and one group of proteins affected may be the proteases of this organism. Work carried out by Packer et al showed that lethal photosensitization using TBO and HeNe laser light does indeed cause a decrease in the proteolytic activity of P. gingivalis (15). This could lead to a reduction in bacterial colonization of the oral cavity (as these proteases are involved in adhesion to host tissues) and less degradation of antibodies, cytokines, and extracellular matrix polymers.…”
Section: Discussionmentioning
confidence: 99%
“…Although PDT is more widely known for its application to the treatment of neoplasms, there is also interest in antimicrobial PDT, as a large number of microorganisms (including oral species) have been reported to be killed in vitro by this approach (21,27,31,40,43,46,47). Furthermore, the potencies of some key virulence factors (lipopolysaccharide and proteases) have also been shown to be reduced by photosensitization (18,32). Due to its localized and noninvasive nature, the side effects associated with many antibiotics (e.g., gastrointestinal disturbance) are unlikely to occur with PDT.…”
mentioning
confidence: 99%